2014
DOI: 10.1038/ncomms5452
|View full text |Cite
|
Sign up to set email alerts
|

A one-dimensional optomechanical crystal with a complete phononic band gap

Abstract: Recent years have witnessed the boom of cavity optomechanics, which exploits the confinement and coupling of optical and mechanical waves at the nanoscale. Among their physical implementations, optomechanical (OM) crystals built on semiconductor slabs enable the integration and manipulation of multiple OM elements in a single chip and provide gigahertz phonons suitable for coherent phonon manipulation. Different demonstrations of coupling of infrared photons and gigahertz phonons in cavities created by inserti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 44 publications
(57 reference statements)
5
141
2
Order By: Relevance
“…Several vibrational modes of the nanobeam structure are coupled to an optical cavity mode (Figure 12(b)) among them some correspond to phonons confined in the cavity (Figure 12(c)). In agreement with the experimental results, 37 the simulations show five families of modes (around 1, 2.5, 4, 5.5 and 7 GHz); in particular a set of modes fall in the absolute band gap around 4 GHz with moderate coupling rates, about 0.4MHz. Details of the experimental measurements and results are presented in refs.…”
Section: Cavity In a Corrugated Nanobeamsupporting
confidence: 88%
See 2 more Smart Citations
“…Several vibrational modes of the nanobeam structure are coupled to an optical cavity mode (Figure 12(b)) among them some correspond to phonons confined in the cavity (Figure 12(c)). In agreement with the experimental results, 37 the simulations show five families of modes (around 1, 2.5, 4, 5.5 and 7 GHz); in particular a set of modes fall in the absolute band gap around 4 GHz with moderate coupling rates, about 0.4MHz. Details of the experimental measurements and results are presented in refs.…”
Section: Cavity In a Corrugated Nanobeamsupporting
confidence: 88%
“…37 The experiments show that the phononic modes around 2.5 GHz with strong optomechanical coupling are almost common to all samples, while higher phononic modes up to 7 GHz are more sensitive to the details of the geometrical structure such as the rounding of the stubs at their basis, the shift in the exact positions of the holes or deviation from their circular shape. Therefore, to explain the effect of the microfabrication imperfections on the very high frequency acoustic modes, it becomes necessary to simulate the exact shape of the nanobeam as obtained from SEM images.…”
Section: Cavity In a Corrugated Nanobeammentioning
confidence: 90%
See 1 more Smart Citation
“…Unlike a pseudo-bandgap for particular symmetry in the frequency range of definition, a full bandgap can prohibit the propagation of phonons regardless of the mode symmetry and the wave vector. The use of a full PNBG is essential to reduce mechanical losses in the PXC structures [25,27]. In the present work, both phononic and photonic modes are calculated by the finite element method (FEM) (COMSOL Multiphysics).…”
Section: Structure and Methodsmentioning
confidence: 99%
“…Psarobas et al [24] reported that a strong AO interaction occurs when acoustic and optical resonant modes are simultaneously confined in a 1D PXC cavity to motivate multi-phonon exchange. Gomis-Bresco et al [25] demonstrated a 1D PXC nanobeam cavity capable of transducing confined phononic modes inside a complete PNBG. Experimental investigations of OM couplings in 2D PXC slabs have also been reported [26,27].…”
Section: Introductionmentioning
confidence: 99%